THE IMPORTANCE OF LEO TOLSTOY'S WORK IN RUSSIAN LITERATURE (ResearchJet Journal of Analysis and Inventions, 2021)
In this article, there are fully information about great writer Leo Tolstoy, his life and his works. All his works are very interesting and meaningful. In addition, there are also some comments and meanings about Leo Tolstoy`s works. Furthermore, there are also information the influence of Leo Tolstoy to great writers and prominent political scientists. Lastly, there are his testament.